(untitled) (Jurnal Bahasa Lingua Scientia, 2011)
The role of correcting errors in English teaching, especially in Speaking class has been debated for a long time. So far the effective method to correct the students’ language errors has not been identified since every English learner has different perception toward the teacher’s correction or feedback. Further, it has not been assured whether the learner’s success in mastering English is solely affected by the correction given. However, there are still some linguists’ views and research finding which can be used to assist the teachers in giving the correction in a Speaking class. At least, there are three ways of correcting errors: selective correction of errors, productive term of error correction and constructive error correction.